Novel method for producing polyspherical graphite, polyspherical graphite produced using same, and secondary battery comprising same as anode active material
By combining natural graphite with asphalt and heat treatment, a spherical graphite with excellent performance was prepared, which solved the problems of uneven shape of spherical graphite and low battery efficiency in the prior art, and achieved efficient battery charging/discharging characteristics and Long life.
Patent Information
- Application Number
- CN202280096230.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-20
- Filing Date
- 2022-09-29
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the production of spherical graphite, the spherical processing of flaky natural graphite causes increased internal stress and defects of particles, reducing the charging/discharge efficiency and life of the battery, and at the same time, a large amount of graphite is discarded, and the uneven shape of the spherical graphite particles affects charging. /Discharge rate efficiency.
After crushing the scale-like natural graphite and asphalt, mixing the binder to form a spherical precursor. After heat treatment and grading, a spherical graphite with uniform particle size and excellent crystallinity can be prepared, and the first 800°C to 1100°C is passed through the first 800°C to 1100°C. A heat treatment and a second heat treatment from 2100°C to 2700°C ensure the crystallinity of graphite and the particle shape.
The produced polyspherical graphite has excellent initial discharge capacity, initial efficiency and high power characteristics, and has a small particle surface pore size and a low internal pore volume, making it suitable as an anode active material for high-performance secondary batteries.
Smart Images

Figure CN119137067A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a novel method for producing spherical graphite, spherical graphite produced using the method, and a secondary battery containing the spherical graphite as an anode active material. Specifically, the present invention relates to a novel method for producing spherical graphite having high initial efficiency, excellent high power characteristics, and a small specific surface area as an anode active material for a secondary battery using natural graphite as a raw material, spherical graphite produced using the method, and a secondary battery containing the spherical graphite as an anode active material. Background Art
[0002] With the recent growth of notebook personal computers, 5G communication-based portable devices such as mobile phones, hybrid electric vehicles (HEVs), and electric vehicles (EVs), the demand for batteries is rapidly increasing.
[0003] In particular, a high-power power source is necessary for hybrid electric vehicles (HEV) and electric vehicles (EV), and thus, there is an increasing demand for batteries having high power characteristics and excellent charge / discharge rates.
[0004] The battery required in this case is a lithium ion secondary battery. In order to achieve high performance of such a lithium secondary battery, a carbonaceous material such as graphite is used for the anode active material of the battery.
[0005] Natural graphite and / or artificial graphite may be used as graphite of a carbonaceous material as an anode active material for a secondary battery.
[0006] On the other hand, for the charge / discharge efficiency of the battery, graphite as a carbonaceous material for an anode active material of a secondary battery advantageously has a spherical form, and more preferably, advantageously has a crystalline spherical form. Various methods for producing spherical graphite for an anode active material of a secondary battery are known.
[0007] In the production of spherical graphite, natural graphite in the form of flakes (plates) has the following disadvantages: due to the increased stress and defects inside the graphite particles caused by the grinding process for the spheroidization process, the capacity decreases during the repeated battery charge / discharge process, thereby deteriorating the life characteristics. In addition, there is a disadvantage that a large amount of natural graphite is discarded in the spheroidization process of plate-shaped natural graphite.
[0008] In addition, as one of the methods for producing spherical graphite, a method has been proposed in which artificial graphite such as coke is coated with a pitch binder material and carbonized to form a carbonaceous layer on its surface, and then spherical graphite is produced through a final graphitization heat treatment (Patent Document 1).
[0009] However, in this method for producing spherical graphite, there is a problem that the shape of spherical graphite particles is not uniform depending on a particulation process, making it insufficient to ensure high efficiency based on a charge / discharge rate (high rate charge / discharge). Summary of the invention
[0010] Technical issues
[0011] An object of the present invention is to provide a method for producing spheroidized graphite used as an anode active material by using natural graphite discarded in the spheroidization process of flaky graphite, wherein the spheroidized graphite is low-cost, has the same properties as those of artificial graphite, and has excellent initial discharge capacity, initial efficiency and high power characteristics of a battery.
[0012] Another object of the present invention is to provide a spherical graphite for use as an anode active material having excellent initial discharge capacity and initial efficiency.
[0013] Still another object of the present invention is to provide a method for producing spheroidized graphite by using natural graphite and the spheroidized graphite obtained by the production method, wherein the spheroidized graphite has a uniform particle size, wherein the crystal particles after the spheroidized graphite is crystallized have a particle size of 2.0 μm. 2 / g or less specific surface area, and the spherical graphite has excellent crystallinity after crystallization, wherein d002 (graphite interlayer distance) representing the degree of crystallization of the spherical graphite particles after crystallization is less than 3.36 Å.
[0014] Solution to the problem
[0015] In order to achieve the above object, the novel method for producing spherical graphite of the present invention comprises:
[0016] (a) a step of pulverizing flaky natural graphite and pitch, respectively ('natural graphite and pitch pulverizing step');
[0017] (b) a step of forming a spheroidized precursor by mixing a binder with the pulverized natural graphite of step (a) ('spheroidized precursor forming step');
[0018] (c) a step of preparing a spheroidized graphite composite by mixing the pulverized pitch of step (a) and a solvent with the spheroidized precursor formed in step (b) ('spheroidized graphite composite preparation step');
[0019] (d) a step of subjecting the spherical graphite composite of step (c) to a first heat treatment at 800° C. to 1100° C. ('first heat treatment step');
[0020] (e) a step of obtaining graphite aggregated into a spherical shape by performing a second heat treatment at a temperature of 2,100° C. to 2,700° C. after the first heat treatment in the step (d) ('second heat treatment step'); and
[0021] (f) A step of obtaining final spherical graphite particles by classifying the spherical graphite obtained by the second heat treatment of step (e) ('classification step').
[0022] In the spherical graphite particles obtained by the method for producing spherical graphite of the present invention comprising the above steps (a) to (f),
[0023] The average particle size (D50) of the spherical graphite particles is less than 18 μm.
[0024] The pore volume inside the spherical graphite particles is less than 0.006 cc / g.
[0025] The pore size of the surface of the spherical graphite particles is less than 18.0 nm.
[0026] The specific surface area of spherical graphite particles is 2.0 m 2 / g or less, and
[0027] d002 (distance between graphite layers), which indicates the degree of crystallinity of the spherical graphite particles, is 3.36 Å or less.
[0028] The spherical graphite particles of the present invention showing the above-mentioned characteristics are used as an anode active material of a secondary battery, and are characterized by having excellent initial discharge capacity, initial efficiency, and high-rate charge / discharge characteristics of the secondary battery.
[0029] Beneficial Effects
[0030] The novel method for producing spheroidized graphite according to the present invention can produce spheroidized graphite that can be used as an anode active material, and the spheroidized graphite has excellent crystallinity, constant particle size, low internal pore volume of spheroidized graphite particles and small pore size on the particle surface, while the method uses natural graphite as a raw material, which is known to have lower initial efficiency and life characteristics than artificial graphite when generally used as an anode active material for batteries. Due to these characteristics, when the spheroidized graphite produced according to the production method of the present invention is used as an anode active material for batteries, it has the following advantages: excellent initial discharge capacity, initial efficiency and high power characteristics of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is a SEM image showing an aggregate of spherical graphite particles produced according to the first embodiment of the method for producing spherical graphite of the present invention.
[0032] Figure 2 is a SEM image showing an aggregate of spherical graphite particles produced according to the second embodiment of the method for producing spherical graphite of the present invention.
[0033] Figure 3 is a SEM image showing an aggregate of spherical graphite particles produced according to a fifth comparative example of the method for producing spherical graphite of the present invention.
[0034] Figure 4 is a SEM image showing an aggregate of spherical graphite particles produced according to a sixth comparative example of the method for producing spherical graphite of the present invention.
[0035] Figure 5 is a FIB image showing spherical graphite particles produced according to the first embodiment of the method for producing spherical graphite of the present invention.
[0036] Figure 6 is a TEM image showing a cross section of spheroidized graphite particles produced according to the first embodiment of the method for producing spheroidized graphite of the present invention.
[0037] Figure 7 It is shown Figure 6 An enlarged TEM image of a portion of a cross section of a spherical graphite particle is shown in FIG.
[0038] Figure 8 It is shown Figure 7 A further magnified TEM image of a portion of a cross section of a spherical graphite particle is shown in FIG.
[0039] Fig. 9 It is shown Figure 8 A further magnified TEM image of a portion of a cross section of a spherical graphite particle is shown in FIG. DETAILED DESCRIPTION
[0040] Hereinafter, only parts necessary for understanding the embodiments of the present invention will be described, and descriptions of other parts will be omitted without obstructing the subject matter of the present invention.
[0041] The terms and expressions used herein should not be interpreted as being limited to conventional or dictionary definitions, but should be considered to be consistent with the meaning and concept of the subject matter of the present invention based on interpretation, based on the principle that the inventor can appropriately define his own invention as the concept of the term to describe it in the best way. Therefore, it should be understood that the embodiments disclosed herein are only exemplary, and various equivalents or improvements thereof are possible.
[0042] The present invention provides a method for producing spheroidized graphite having excellent crystal properties, uniform particle size, very small particle internal pore volume and small pore size on the particle surface.
[0043] The novel method for producing spherical graphite according to the present invention comprises:
[0044] (a) a step of pulverizing flaky natural graphite and pitch, respectively ('natural graphite and pitch pulverizing step');
[0045] (b) a step of forming a spheroidized precursor by mixing a binder with the pulverized natural graphite of step (a) ('spheroidized precursor forming step');
[0046] (c) a step of preparing a spheroidized graphite composite by mixing the pulverized pitch of step (a) and a solvent with the spheroidized precursor formed in step (b) ('spheroidized graphite composite preparation step');
[0047] (d) a step of subjecting the spherical graphite composite of step (c) to a first heat treatment at 800° C. to 1100° C. ('first heat treatment step');
[0048] (e) a step of obtaining graphite aggregated into a spherical shape by performing a second heat treatment at a temperature of 2,100° C. to 2,700° C. after the first heat treatment in the step (d) ('second heat treatment step'); and
[0049] (f) A step of obtaining final spherical graphite particles by classifying the spherical graphite obtained by the second heat treatment of step (e) ('classification step').
[0050] Hereinafter, steps (a) to (f) will be described in detail.
[0051] The 'natural graphite and pitch pulverizing step' in step (a) is a step of pulverizing natural graphite and pitch, respectively. The 'natural graphite' as the target of pulverization may have an average particle size of 5 μm to 500 μm, preferably 5 μm to 100 μm, and when the average particle size exceeds 500 μm, it is economically undesirable because the total pulverization process time increases.
[0052] In addition, 'asphalt' as a target of pulverization may have an average particle size of 20 mm or less, preferably 10 mm, and when the average particle size exceeds 20 mm, it is economically undesirable because the total pulverization process time increases.
[0053] The pulverization of each of the 'natural graphite' and the 'asphalt' in step (a) can be carried out using a high-speed mechanical grinder such as a hammer mill, a jet mill, a bead mill or a combination thereof, preferably a jet mill. In this case, the operating pressure of the hammer mill, the jet mill or the bead mill is the pressure required by each mill, and the pressure in the case of pulverization using a jet mill is 5 to 10 bars, preferably 7 to 10 bars.
[0054] In addition, as described above, natural graphite particles having an average particle size of 1 to 10 μm, preferably 1 to 5 μm, are prepared from flaky natural graphite by a pulverization process using a jet mill, etc. The prepared natural graphite particles having an average particle size of 1 to 10 μm are referred to as 'pulverized natural graphite'.
[0055] On the other hand, the asphalt in step (a) is petroleum-based asphalt, coal-based asphalt or polymer resin, preferably petroleum-based asphalt.
[0056] The pulverization of the asphalt is carried out using a high-speed mechanical grinding machine such as a hammer mill, a jet mill, a bead mill or a combination thereof, preferably a jet mill. In this case, the working pressure of the hammer mill, the jet mill or the bead mill is the pressure required by each mill, and the pressure in the case of pulverization using a jet mill is 5 to 10 bars, preferably 6 to 10 bars.
[0057] In addition, as described above, asphalt particles having an average particle size of 1 to 10 μm, preferably 1 to 5 μm, are prepared from asphalt through a pulverization process using a jet mill, etc. The prepared asphalt particles having an average particle size of 1 to 10 μm are referred to as 'pulverized asphalt'.
[0058] The 'spherical precursor formation step' of step (b) is divided into:
[0059] i) a crushed natural graphite and binder mixing step, wherein a 'binder' is mixed with the 'crushed natural graphite' of step (a);
[0060] ii) a step of forming said spheroidized precursor from the mixture obtained from the mixing step i); and
[0061] iii) a step of drying the spheroidized precursor obtained from the spheroidized precursor forming step ii).
[0062] The binder in the crushed natural graphite and binder mixing step i) may be 'hydrocarbon oil', 'silicone oil', 'vegetable oil', 'triglyceride' or a mixture thereof, preferably 'hydrocarbon oil' or 'silicone oil', and more preferably 'hydrocarbon oil'.
[0063] 'Hydrocarbon oil' may include: petroleum oils, such as paraffin oil, petrolatum (Vaseline) and isoparaffin; synthetic oils, such as hydrogenated polydecene, synthetic squalane and polybutene; vegetable oils, such as vegetable squalane and hydrogenated squalane, and the like.
[0064] A preferred 'hydrocarbon oil' may be 'paraffin oil'.
[0065] In the pulverized natural graphite and binder mixing step i), the binder is used in an amount of 15 to 25 parts by weight, and preferably 20 parts by weight, relative to 100 parts by weight of the pulverized natural graphite.
[0066] In the mixing step i), the mixing time is the time until the mixing of the 'pulverized natural graphite' and the 'binder' is completely achieved, and can be determined according to the amounts used. A preferred mixing time is 1 hour or more.
[0067] The above mixing can be performed using a paddle mixer, which is a typical mixer in the art.
[0068] The spherical precursor forming step ii) is a step of placing the mixture of the mixing step i) into a conglomerating machine, and then performing a spherical process at a line speed of 3,500 m / min to 6,000 m / min, preferably 4,000 m / min to 5,000 m / min for 100 seconds to 5,000 seconds, preferably 500 seconds to 3,000 seconds, and more preferably 500 seconds to 2,000 seconds.
[0069] The pelletizer is a rotatable device known in the art, and is preferably a spheronizing device having blades formed on a rotor to apply friction and shear stress to the mixture during rotation. The spheronization of the pulverized graphite appears to be caused by the friction and shear stress applied to the mixture.
[0070] The drying step iii) is a step of drying the spherical precursor obtained by the pelletizing process of the mixture in step ii) at 300° C. to 1000° C., preferably 400° C. to 700° C., for 30 minutes to 2 hours, preferably 1 hour to 1.5 hours. In the drying step iii), the binder mixed with the natural graphite is removed.
[0071] In the above step (b) of forming a spheroidized precursor, a dried spheroidized precursor is obtained by the following steps: i) mixing pulverized natural graphite and a binder; ii) forming a spheroidized precursor; and iii) drying the formed spheroidized precursor.
[0072] The 'spheroidized graphite composite preparation step' of step (c) is a step of preparing a spheroidized graphite composite by treating the spheroidized precursor formed and dried in step (b) with a mixed solution of the pulverized pitch of step (a) and a solvent.
[0073] The amount of the pulverized pitch is 25 to 35 parts by weight, preferably 30 parts by weight, relative to 100 parts by weight of the pulverized natural graphite.
[0074] If the amount of pitch is less than 25 parts by weight, the crystallinity of the finished spherical graphite is reduced. This may make the anode active material production process unstable, such as the particles of the spherical graphite being broken during the pressurization process, and may also cause the initial discharge capacity and initial efficiency to be low due to the increased specific surface area (see the first comparative example and the second comparative example).
[0075] In addition, if the amount of pitch used is greater than 35 parts by weight, when the spheroidized graphite precursor is treated with a mixed solution of pitch and a solvent in the spheroidized graphite precursor forming step (b), the entire precursor becomes agglomerated, whereby progress after step (b) becomes unfeasible. Therefore, there is a disadvantage that spheroidized graphite in the form of powder that can be used as an anode material cannot be obtained (see the fifth comparative example).
[0076] The solvent in the 'spherical graphite composite preparation step' of step (c) is a solvent capable of dissolving pitch, preferably an organic solvent, more preferably an ether, and even more preferably tetrahydrofuran (THF).
[0077] The amount of the solvent used is 100 to 400 parts by weight, preferably 200 to 300 parts by weight, relative to 100 parts by weight of the pulverized natural graphite of step (a).
[0078] If the amount of the solvent used is less than 100 parts by weight, the surface of the dried spheroidized precursor is poorly treated due to the pulverized pitch dissolved in the solvent. As a result, the surface treatment of the natural graphite with the pitch is only partially performed. Therefore, pelletization is not completely performed, so the production efficiency of the spheroidized graphite may be reduced, and there is a disadvantage that the performance of the obtained spheroidized graphite may be reduced.
[0079] If the amount of the solvent used is greater than 400 parts by weight, there is a disadvantage that the economic feasibility of the process is reduced depending on the solvent removal time.
[0080] In particular, in the case of a drying process without using a solvent, after the first heat treatment step (d), the mixture of the spheroidized precursor and asphalt becomes agglomerated, making it impossible to obtain spheroidized graphite in powder form that can be used as an anode material (see the sixth comparative example).
[0081] Specifically, the 'step of preparing the graphite composite aggregated into a spherical shape' of step (c) is as follows.
[0082] First, the step is to mix the spherical precursor formed in step (b) with a mixed liquid of the crushed asphalt of step (a) dissolved in a solvent, and stir them in a stirrer, thereby wet-treating the surface of the spherical precursor formed in step (b) with the mixed liquid.
[0083] The stirring is performed by stirring and mixing using a mixer such as a screw mixer (eg, Nauta mixer).
[0084] The stirring time is the time for which the dried spherical precursor is fully mixed in the mixed solution in which the pulverized asphalt is dissolved in the solvent. The stirring time may be 30 minutes to 2 hours, but it may be changed according to the total amount.
[0085] Next, after the stirring in the stirrer is completed, drying is performed while distilling and recovering the solvent by heating at a temperature of 100° C. to 150° C. under a vacuum of 10 mbar to 100 mbar, preferably 10 mbar to 50 mbar.
[0086] The dried spherical graphite composite is pulverized by a pulverizing process using a pin pulverizer.
[0087] The first heat treatment step (d) is a step of subjecting the pulverized spheroidized graphite composite obtained in step (c) to a first heat treatment at a temperature of 800° C. to 1,100° C., preferably at a temperature of 1,000° C. to obtain first heat-treated spheroidized graphite.
[0088] The first heat treatment is performed in a nitrogen atmosphere, and an electric furnace, which is a typical heat treatment apparatus, may be used.
[0089] The time of the first heat treatment is about 30 minutes to 2 hours, and may be changed according to the amount of the pulverized spherical graphite composite subjected to the first heat treatment.
[0090] The second heat treatment step (e) is a step of subjecting the graphite spheroidized by the first heat treatment in the step (d) to a secondary heat treatment at a temperature of 2,100°C to 2,700°C.
[0091] If the second heat treatment temperature is lower than 2100° C., d002 (distance between graphite layers) exceeds 3.36 Å, and the initial discharge capacity and initial efficiency of the spherical graphite obtained thereby decrease (see the third comparative example).
[0092] If the second heat treatment temperature is higher than 2700° C., the second heat treatment process requires high temperature heat, and thus the process is less economical.
[0093] On the other hand, the second heat treatment is a step of crystallizing amorphous carbon such as carbonized pitch and natural graphite in the spheroidized graphite formed by the first heat treatment of step (d), and the crystallization of the spheroidized graphite is further improved (low d002 value) by the second heat treatment. This excellent crystallization of the spheroidized graphite is conducive to the process of producing anode active materials, and in addition, it causes the effect of providing excellent initial discharge capacity, initial efficiency and high power characteristics (see first and second embodiments).
[0094] The crystallinity of the spheroidized graphite that is not subjected to the second heat treatment step (e) becomes lower (high d002 value, see the fourth comparative example), so that the produced spheroidized graphite has an increased irreversible capacity during the initial charge / discharge period, resulting in lower initial efficiency and lower charge / discharge life characteristics. In addition, the pore volume inside the spheroidized graphite particles and the pore size on the surface of the spheroidized graphite particles increase, resulting in the disadvantage of reducing high-power characteristics. This is not conducive to the production of anode active materials, especially for the production of anode active materials for batteries requiring high power (see the fourth comparative example).
[0095] The second heat treatment is performed in an argon atmosphere, and an electric furnace, which is a typical heat treatment apparatus, may be used.
[0096] The second heat treatment time is about 30 minutes to 2 hours, and may be changed according to the amount of the first heat-treated spherical graphite to be subjected to the second heat treatment.
[0097] 'Classification step' (f) is a step of obtaining a final spherical graphite anode material by classifying the spherical graphite obtained by the second heat treatment step (e).
[0098] This classification is performed using a 325-mesh screen classifier to obtain final spherical graphite having a particle size with an average particle size (D50) of 18 μm or less.
[0099] As described above, the method for producing spheroidized graphite of the present invention, which includes steps (a) to (f), is to produce a spheroidized precursor using flaky, crushed natural graphite and a binder, and then prepare a crushed spheroidized graphite composite by stirring the spheroidized precursor with a mixture of crushed asphalt and a solvent, drying and crushing its surface (steps (a) to (c)); obtain spheroidized graphite by first heating the prepared crushed spheroidized graphite composite (step (d)); crystallize the spheroidized graphite obtained by the first heating by a second heat treatment (step (e)); and then classify to finally obtain spheroidized graphite with a particle size of less than 18 μm (step (f)).
[0100] In the spherical graphite particles obtained by the method for producing spherical graphite of the present invention comprising the above steps (a) to (f),
[0101] The average particle size (D50) of the spherical graphite particles is less than 18 μm.
[0102] The pore volume inside the spherical graphite particles is less than 0.006 cc / g.
[0103] The pore size of the surface of the spherical graphite particles is less than 18.0 nm, and
[0104] The specific surface area of spherical graphite particles is 2.0 m 2 / g or less, preferably 1.4 m 2 / g or less.
[0105] In addition to the above characteristics, the d002 (inter-graphite distance) representing the degree of crystallinity of the spherical graphite particles of the present invention is less than 3.36 Å, that is, the spherical graphite particles have excellent crystallinity. Therefore, the granulation of the spherical graphite particles is maintained even under the strong pressure applied during the production of the anode active material, thereby showing excellent initial discharge capacity (%) and initial efficiency (%) of the battery.
[0106] The spherical graphite particles of the present invention showing the above-mentioned characteristics are used as an anode active material of a secondary battery, thereby having excellent initial discharge capacity and excellent high-rate charge / discharge characteristics of the secondary battery.
[0107] The SEM image of the spheroidized graphite obtained by the method for producing spheroidized graphite of the present invention comprising steps (a) to (f) is shown in FIG. Figure 1 and 2 Shown in. Figure 1 and 2 It can be seen from the SEM image that the spherical graphite obtained by the production method of the present invention exhibits a spherical shape.
[0108] In addition, if Figure 5 As shown, it can be seen that the spherical graphite produced by the production method of the present invention has an almost perfect spherical shape.
[0109] In addition, if Figures 6 to 9 As shown, it can be seen that the pitch is coated on the outside of the spherical graphite produced by the production method of the present invention.
[0110] In this way, the spheroidized graphite produced by the production method according to the present invention has an almost perfect spherical shape, the pitch is formed by coating the outside of the spherical shape, and the natural graphite is densely formed inside the spheroidized graphite.
[0111] The fact that natural graphite is densely formed inside the spheroidized graphite is caused by using a binder in the pulverized natural graphite. That is, the pulverized natural graphite is perfectly spheroidized by the binder, which leads to the formation of a spheroidized precursor (see step (b) of the method for producing spheroidized graphite according to the present invention).
[0112] As a result of the production steps, the physical properties of the finally produced spheroidized graphite, such as pore volume and pore size, are reduced, resulting in excellent high power characteristics.
[0113] In addition, the formation of pitch on the outer surface of the spheroidized graphite having an almost perfect spherical shape is the result of treating the spheroidized precursor with an appropriate amount of pitch and a wet method, and therefore, the physical properties of the finally produced spheroidized graphite, such as the D002 value indicating the degree of crystallinity, are reduced. Therefore, the spheroidized graphite of the present invention has the advantage of being able to be used as an excellent anode material even under the pressure of a battery production process.
[0114] Implementation Description
[0115] Hereinafter, the present invention will be further described through various embodiments. The following embodiments are intended to illustrate or specifically describe the present invention, and the scope of the present invention is not limited thereto.
[0116] In addition, since contents not described herein can be sufficiently inferred by those skilled in the art, descriptions thereof will be omitted.
[0117] <First embodiment>
[0118] After the pulverizing pressure of the air jet mill is set to 6 to 8 bar, petroleum-based asphalt with an average particle size of 5 mm is pulverized to an average particle size of 4 μm, and after the pulverizing pressure of the air jet mill is set to 6 to 8 bar, flaky natural graphite with an average particle size of 100 μm is pulverized to an average particle size of 3 μm (step (a)).
[0119] 10 kg of pulverized graphite and 2 kg of paraffin oil were placed in a paddle mixer and mixed for 1 hour. 6 kg of the obtained mixture was placed in a pelletizer and pelletized for 600 seconds at a line speed of 4,500 m / min. 6 kg of the pelletized precursor was recovered and then placed in a dryer and dried at 500° C. for 1 hour to obtain a pelletized precursor (step (b)).
[0120] 5 kg of the obtained spheroidized precursor was placed in a Nauta mixer. 1.5 kg of crushed petroleum-based asphalt (corresponding to 30 parts by weight / 100 parts by weight of the graphite in step (a)) was placed in 13.5 kg of THF and dissolved, and then placed in a Nauta mixer containing 5 kg of the precursor and stirred for 1 hour. When the stirring was completed, THF was distilled and recovered while heating at 130° C. under a vacuum of 40 mbar, and dry mixed to obtain a spheroidized graphite composite. The spheroidized graphite composite obtained when the dry mixing was completed was pin-crushed to crush the particles (step (c)).
[0121] The obtained pulverized spheroidized graphite composite was put into an electric furnace and heat-treated at 1000° C. in a nitrogen atmosphere to obtain spheroidized graphite. The heat treatment time at 1000° C. was set to 1 hour (step (d)).
[0122] After the heat treatment at 1000° C. was completed, the graphite spheroidized by the first heat treatment was put back into the electric furnace and subjected to a second heat treatment at 2400° C. in an argon atmosphere for 1 hour (step (e)).
[0123] The spheroidized graphite that had completed the second heat treatment at 2400° C. was classified by a 325-mesh screen classifier, thereby finally producing a spheroidized graphite anode material (step (f)).
[0124] For the spherical graphite finally produced through steps (a) to (f), the average particle size (D50, μm), specific surface area (m 2 / g), graphite interlayer distance (d002, Å) (by XRD analysis), pore volume and pore size. In addition, a button battery half-cell using spherical graphite as an anode active material was produced, and the initial discharge capacity (0.2C discharge capacity, mAh / g), initial efficiency (%), 3C discharge capacity (mAh / g) and high rate charge / discharge characteristics (high power characteristics, 3C / 0.2C, %) of the battery were measured (see Tables 1 and 2).
[0125] <Second Implementation Method>
[0126] The final spheroidized graphite was produced in the same manner as in the first embodiment, except that the 'second heat treatment temperature of step (e)' in the first embodiment was set to "2,600°C".
[0127] For the spherical graphite finally produced through steps (a) to (f), the average particle size (D50, μm), specific surface area (m 2 / g), graphite interlayer distance (d002, Å) (by XRD analysis), pore volume and pore size. In addition, a button battery half-cell using spherical graphite as an anode active material was produced, and the initial discharge capacity (0.2C discharge capacity, mAh / g), initial efficiency (%), 3C discharge capacity (mAh / g) and high rate charge / discharge characteristics (high power characteristics, 3C / 0.2C, %) of the battery were measured (see Tables 1 and 2).
[0128] <First Comparative Example>
[0129] The final spherical graphite is produced in the same manner as in the first embodiment, except that the amounts of pulverized pitch and THF in step (c) are 1.0 kg (corresponding to 20 parts by weight per 100 parts by weight of graphite in step (a)) and 9.0 kg, respectively.
[0130] For the spherical graphite finally produced through steps (a) to (f), the average particle size (D50, μm), specific surface area (m 2 / g), graphite interlayer distance (d002, Å) (by XRD analysis), pore volume and pore size. In addition, a button battery half-cell using spherical graphite as an anode active material was produced, and the initial discharge capacity (0.2C discharge capacity, mAh / g), initial efficiency (%), 3C discharge capacity (mAh / g) and high rate charge / discharge characteristics (high power characteristics, 3C / 0.2C, %) of the battery were measured (see Tables 1 and 2).
[0131] <Second Comparative Example>
[0132] The final spherical graphite is produced in the same manner as in the first embodiment, except that the amounts of pulverized pitch and THF in step (c) are 0.5 kg (corresponding to 10 parts by weight / 100 parts by weight of graphite in step (a)) and 4.5 kg, respectively.
[0133] For the spherical graphite finally produced through steps (a) to (f), the average particle size (D50, μm), specific surface area (m 2 / g), graphite interlayer distance (d002, Å) (by XRD analysis), pore volume and pore size. In addition, a button battery half-cell using spherical graphite as an anode active material was produced, and the initial discharge capacity (0.2C discharge capacity, mAh / g), initial efficiency (%), 3C discharge capacity (mAh / g) and high rate charge / discharge characteristics (high power characteristics, 3C / 0.2C, %) of the battery were measured (see Tables 1 and 2).
[0134] <Third Comparative Example>
[0135] The final spheroidized graphite was produced in the same manner as in the first embodiment, except that the 'second heat treatment temperature of step (e)' in the first embodiment was set to "2,000°C".
[0136] For the spherical graphite finally produced through steps (a) to (f), the average particle size (D50, μm), specific surface area (m 2 / g), graphite interlayer distance (d002, Å) (by XRD analysis), pore volume and pore size. In addition, a button battery half-cell using spherical graphite as an anode active material was produced, and the initial discharge capacity (0.2C discharge capacity, mAh / g), initial efficiency (%), 3C discharge capacity (mAh / g) and high rate charge / discharge characteristics (high power characteristics, 3C / 0.2C, %) of the battery were measured (see Tables 1 and 2).
[0137] <Fourth Comparative Example>
[0138] The final spheroidized graphite is produced in the same manner as in the first embodiment, except that the 'second heat treatment' (which is step (e) in the first embodiment) is not performed.
[0139] For the spherical graphite finally produced through steps (a) to (f), the average particle size (D50, μm), specific surface area (m 2 / g), graphite interlayer distance (d002, Å) (by XRD analysis), pore volume and pore size. In addition, a button battery half-cell using spherical graphite as an anode active material was produced, and the initial discharge capacity (0.2C discharge capacity, mAh / g), initial efficiency (%), 3C discharge capacity (mAh / g) and high rate charge / discharge characteristics (high power characteristics, 3C / 0.2C, %) of the battery were measured (see Tables 1 and 2).
[0140] <Fifth Comparative Example>
[0141] The final spherical graphite was produced in the same manner as in the first embodiment except that the amounts of pulverized pitch and THF in step (c) were 2.0 kg (corresponding to 40 parts by weight / 100 parts by weight of graphite in step (a)) and 18.0 kg, respectively. In addition, due to this amount of pitch, a hard lump was formed after step (c), and therefore, the first heat treatment step (d), the second heat treatment step (e) and the classification step (f) could not be performed.
[0142] For the spherical graphite finally produced through steps (a) to (f), the average particle size (D50, μm), specific surface area (m 2 / g), graphite interlayer distance (d002, Å) (by XRD analysis), pore volume and pore size. In addition, a button battery half-cell using spherical graphite as an anode active material was produced, and the initial discharge capacity (0.2C discharge capacity, mAh / g), initial efficiency (%), 3C discharge capacity (mAh / g) and high rate charge / discharge characteristics (high power characteristics, 3C / 0.2C, %) of the battery were measured (see Tables 1 and 2).
[0143] <Sixth Comparative Example>
[0144] The final spheroidized graphite was produced in the same manner as in the first embodiment except that THF as a solvent was not used (dry treatment was performed without using a solvent) in the spheroidized graphite composite preparation step of step (c) in the first embodiment.
[0145] For the spherical graphite finally produced through steps (a) to (f), the average particle size (D50, μm), specific surface area (m2 / g), graphite interlayer distance (d002, Å) (by XRD analysis), pore volume and pore size. In addition, a button battery half-cell using spherical graphite as an anode active material was produced, and the initial discharge capacity (0.2C discharge capacity, mAh / g), initial efficiency (%), 3C discharge capacity (mAh / g) and high rate charge / discharge characteristics (high power characteristics, 3C / 0.2C, %) of the battery were measured (see Tables 1 and 2).
[0146] <Seventh Comparative Example>
[0147] For 5 kg of spherical graphite (natural spherical graphite from Weida, China, with an average particle size D50 of 12.7 um and a specific surface area of 6.6 m 2 / g), using '0.5 kg (corresponding to 10 parts by weight / 100 parts by weight of graphite) and 4.5 kg' of pulverized pitch and THF, respectively, steps (c) to (f) of the first embodiment are carried out in the same manner to produce the final spherical graphite anode material.
[0148] For the spherical graphite finally produced through steps (a) to (f), the average particle size (D50, μm), specific surface area (m 2 / g), graphite interlayer distance (d002, Å) (by XRD analysis), pore volume and pore size. In addition, a button battery half-cell using spherical graphite as an anode active material was produced, and the initial discharge capacity (0.2C discharge capacity, mAh / g), initial efficiency (%), 3C discharge capacity (mAh / g) and high rate charge / discharge characteristics (high power characteristics, 3C / 0.2C, %) of the battery were measured (see Tables 1 and 2).
[0149] Table 1 below shows the process conditions of the first embodiment and the second embodiment and the first to seventh comparative examples. Table 2 below shows the average particle size (D50, μm), specific surface area (m 2 / g), graphite interlayer distance (d002, Å) (analyzed by XRD), pore volume and pore size.
[0150] For the average particle size (D50), the particle size was measured using a particle size analyzer from Anton Paar, and the specific surface area (m 2 / g) was measured using a BET device from Micromertics.
[0151] In addition, the graphite interlayer distance d002 (Å) was measured as the stacking distance of each carbon hexagonal grid plane obtained by XRD analysis, and was calculated as follows.
[0152] d002 = λ / 2(sinθ), λ: wavelength of Cu (X-ray target) (1.5406A)
[0153] θ: Typical 002 in graphite is 26.554 2θ
[0154] <Manufacturing of button batteries>
[0155] The slurry was prepared by mixing the spherical graphite anode active material: SBR: CMC in each of the first embodiment and the second embodiment and the first to seventh comparative examples in ultrapure water at a ratio of 97: 1.5: 1.5. The slurry was uniformly coated on a copper foil, dried in an oven at 80° C. for about 2 hours, then rolled, and further dried in a vacuum oven at 110° C. for about 12 hours to prepare an anode plate.
[0156] A CR2032 button-type half-cell was prepared using: the prepared anode plate; a lithium foil as a counter electrode; a porous polypropylene film separator; and a liquid electrolyte in which LiPF6 was dissolved at a concentration of 1.2 M in a solvent in which ethylene carbonate and diethyl carbonate (DEC) were mixed in a volume ratio of 3:7.
[0157] <Measurement of initial discharge capacity (mAh / g) and initial efficiency (%) of button batteries>
[0158] Apply constant current at 0.1C rate at 25℃ until the battery voltage reaches 0.01V (vs. Li). When the battery voltage reaches 0.01V, apply constant voltage to charge until the current reaches 0.01C rate. Discharge at constant current of 0.2C rate until the voltage reaches 1.5V (vs. Li).
[0159] <Measurement of high power characteristics of button batteries>
[0160] The discharge rate of the high power characteristic is expressed as a relative value by measuring the discharge capacity under 3C and 0.2C conditions.
[0161] The following Table 1 shows the input amounts of natural graphite and a binder as a spherical graphite precursor raw material, the input amounts of asphalt and a solvent used in the surface treatment process, and the first heat treatment temperature and the second heat treatment temperature in the first and second embodiments and the first to seventh comparative examples.
[0162] [Table 1]
[0163]
[0164] * Note 1: After the surface treatment process, it is discarded as a hard block and therefore cannot be subjected to additional heat treatment (see Figure 3 )
[0165] ** Note 2: After the 1,000°C heat treatment, it was discarded as a hard block, so it could not be subjected to the second heat treatment (see Figure 4 )
[0166] Table 1 shows process conditions regarding the first embodiment and the second embodiment of the method for producing spherical graphite of the present invention including the above-mentioned steps (a) to (f), and the first to seventh comparative examples.
[0167] Specifically, in the first and second embodiments of the present invention, the content of asphalt used for surface treatment is 30 parts by weight relative to 100 parts by weight of natural graphite in the spherical graphite precursor of the natural graphite and the binder, and in the first comparative example, the second comparative example and the fifth comparative example, the content is 20 parts by weight, 10 parts by weight and 40 parts by weight, respectively. The amount of asphalt used in the first comparative example, the second comparative example and the fifth comparative example is outside the range of 25 parts by weight to 35 parts by weight relative to 100 parts by weight of natural graphite, which is the amount of asphalt used in the present invention.
[0168] In addition, the second heat treatment temperature of the third comparative example was set to 2,000° C., which is outside the range of “2,100° C. to 2,700° C.” of the second heat treatment temperature of the present invention. In addition, in the fourth comparative example, only the first heat treatment was performed, and the second heat treatment was omitted.
[0169] In the sixth comparative example, the surface treatment of the spherical graphite precursor uses a dry surface treatment process, that is, only pitch is used without using a solvent, and in the seventh comparative example, a wet surface treatment of the surface of the spherical graphite is used.
[0170] The results obtained by the production methods of the first and second embodiments and the fourth and fifth comparative examples are Figures 1 to 4 Shown in.
[0171] like Figure 1 and 2 As shown, it can be seen that the spheroidized graphite produced by the first embodiment and the second embodiment is granular spheroidized graphite.
[0172] However, if Figure 3 and 4 As shown, in the case of using an excessive amount of pitch beyond the scope of the present invention in the fifth comparative example, and in the case of dry processing without using a solvent, granulation of graphite aggregated into a spherical shape is not formed, making it almost impossible to use it as an anode material.
[0173] in addition, Figures 5 to 9 TEM images of the cross section and the surface of spherical graphite particles produced by the first embodiment of the present invention are shown.
[0174] like Figures 5 to 9 As shown, it can be seen that the spherical graphite produced by the production method of the present invention has an almost perfect spherical shape (see Figure 5 ), natural graphite is densely formed inside the spherical graphite (see Figure 8 and 9 ), and only the outside of the spherical natural graphite is densely formed and coated with pitch (see Figure 8 and 9 ).
[0175] Figures 5 to 9 The spheroidized graphite of the present invention shown in is spheroidized graphite produced by utilizing the characteristics of each step of the method for producing spheroidized graphite of the present invention.
[0176] Therefore, due to Figures 5 to 9 Due to the uniqueness shown in, that is, the fact that natural graphite is densely formed inside the spherical graphite particles and asphalt is formed only outside the spherical natural graphite, the spherical graphite of the present invention has the advantages of excellent high power characteristics due to the reduced pore volume and pore size (which are physical properties), and because the D002 value indicating the degree of crystallinity is reduced, the spherical graphite of the present invention has the advantage of being able to be used as an excellent anode material even under the pressure of the battery production process.
[0177] Table 2 below shows the physical properties of the spherical graphite produced under the process conditions of Table 1 in the first embodiment and the second embodiment and the first to seventh comparative examples, namely, pore volume (cc / g), pore size (nm), particle size (D50, μm), specific surface area (m 2 / g) and d002 (nm, graphite interlayer distance), and also show the initial discharge capacity (%), initial efficiency (%) and high rate discharge characteristics (high power characteristics, %) of a battery using the spherical graphite as an anode active material.
[0178] [Table 2]
[0179]
[0180] As can be seen from Table 2, the first and second embodiments of the method for producing spherical graphite of the present invention have higher initial discharge capacity at 0.2C and higher initial discharge capacity at 3C than the first to seventh comparative examples, and therefore, the power characteristics representing the high power characteristics of the battery are 97.2% and 96.9%, respectively, which are far superior to 86.2% to 92.8% of the first to sixth comparative examples. In particular, the present invention shows a high power characteristic that is improved by almost 50% or more compared to 64.6% of the seventh comparative example (the seventh comparative example is a conventional technique in which the surface of spherical graphite is treated with pitch).
[0181] Therefore, the high 0.2C and 3C initial efficiencies of the spheroidized graphite according to the first and second embodiments of the present invention and its high power characteristics indicate that the spheroidized graphite according to the first and second embodiments of the present invention can be used as anode materials for batteries in fields requiring initial high power, especially in automotive vehicles.
[0182] As described above, the method for producing spherical graphite according to the first embodiment and the second embodiment of the present invention can produce spherical graphite having excellent initial efficiency and high power characteristics when used as an anode active material for a battery, and the spherical graphite having such characteristics can be used as an excellent anode active material for batteries (especially motor vehicle batteries), and therefore has industrial applicability.
[0183] Industrial Applicability
[0184] Therefore, the spherical graphite of the present invention can be used as an excellent anode active material for batteries (especially automotive batteries), and thus has industrial applicability. In addition, a battery containing the spherical graphite has industrial applicability, especially industrial applicability for automotive vehicles.
Claims
1. A method for producing spherical graphite, the method comprising: include: (a) a step of pulverizing flaky natural graphite and pitch, respectively ('natural graphite and pitch pulverizing step'); (b) a step of forming a spheroidized precursor by mixing a binder with the pulverized natural graphite of step (a) ('spheroidized precursor forming step'); (c) a step of preparing a spheroidized graphite composite by mixing the pulverized pitch of step (a) and a solvent with the spheroidized precursor formed in step (b) ('spheroidized graphite composite preparation step'); (d) a step of subjecting the spherical graphite composite of step (c) to a first heat treatment at 800° C. to 1100° C. ('first heat treatment step'); (e) a step of obtaining graphite aggregated into a spherical shape by performing a second heat treatment at a temperature of 2,100° C. to 2,700° C. after the first heat treatment in the step (d) ('second heat treatment step'); and (f) A step of obtaining final spherical graphite particles by classifying the spherical graphite obtained by the second heat treatment of step (e) ('classification step').
2. The method according to claim 1, wherein the step (b) is divided into: i) a crushed natural graphite and binder mixing step, wherein a 'binder' is mixed with the 'crushed natural graphite' of step (a); ii) a step of forming said spheroidized precursor from the mixture obtained from the mixing step i); and iii) drying the spheroidized precursor obtained from the spheroidized precursor forming step ii), wherein in the step i) of mixing the crushed natural graphite and the binder, the amount of the binder is 15 to 25 parts by weight relative to 100 parts by weight of the crushed natural graphite, and The step ii) of forming the precursor into a spherical shape comprises placing the mixture of the mixing step i) into a spheronizer, and then performing a spheronization process at a line speed of 3,500 m / min to 6,000 m / min for 100 seconds to 5,000 seconds.
3. The method according to claim 1, wherein in the 'spherical graphite composite preparation step' (c), the amount of the pulverized pitch is 25 to 35 parts by weight relative to 100 parts by weight of the pulverized natural graphite of step (a), and The amount of the solvent is 100 to 400 parts by weight relative to 100 parts by weight of the pulverized natural graphite in step (a).
4. The method according to claim 1, wherein in the spherical graphite particles obtained in the 'classification step' (f), the average particle size (D50) is 18 μm or less, and The specific surface area of the spherical graphite particles is 2.0 m 2 / g or less.
5. The method according to claim 1, wherein in the spherical graphite particles obtained in the 'classification step' (f), The pore volume inside the spherical graphite particles is less than 0.006 cc / g, and The pore size on the surface of the spherical graphite particles is less than 18.0 nm.
6. The method according to claim 1, wherein in the spherical graphite particles obtained in the 'classification step' (f), d002 (distance between graphite layers) indicating the degree of crystallinity of the spherical graphite particles is 3.36 Å or less.
7. The method according to claim 1, wherein the asphalt in step (b) is 'petroleum-based asphalt', 'coal-based asphalt' or 'polymer resin', and The binder in step (b) is 'hydrocarbon oil', 'silicone oil', 'vegetable oil', 'triglyceride' or a mixture thereof.
8. The method according to claim 1, wherein in the 'natural graphite and pitch pulverizing step' (a), The natural graphite particles having an average particle size of 5 μm to 500 μm are crushed to an average particle size of 1 μm to 10 μm, and The asphalt particles having an average particle size of 20 mm or less are crushed to an average particle size of 1 μm to 10 μm.
9. Spheroidized graphite produced by the method for producing spheroidized graphite according to any one of claims 1 to 8. 10 . A secondary battery using the spherical graphite according to claim 9 as an anode active material. 11 . The secondary battery according to claim 10 , wherein a high rate charge / discharge characteristic (high power characteristic, 3C / 0.2C, %) of the secondary battery is 95% or more. 12 . The secondary battery according to claim 10 , wherein the secondary battery is a battery for a motor vehicle.
Citation Information
Patent Citations
Negative electrode active material and negative electrode for lithium ion rechargeable battery
CN101507019A
Natural graphite composite material, preparation method thereof and lithium ion battery
CN106058211A
Carbon material, method for producing carbon material, and non-aqueous secondary battery using carbon material
CN106663808A
Negative electrode material for lithium ion secondary battery, and method of manufacturing negative electrode material for lithium ion secondary battery
CN111492515A
Composite carbon negative electrode material of lithium ion power battery and its preparation method
CN1885598A
